2014
DOI: 10.20870/oeno-one.2014.48.4.1694
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between carbohydrates and reproductive development in chardonnay grapevine: impact of defoliation and fruit removal treatments during four successive growing seasons

Abstract: <p style="text-align: justify;"><strong>Aim</strong>: The present study was conducted in grapevines to evaluate the influence of source/sink disturbance on reserve restoration in the entire plant (trunk, roots) and the consequences on reproduction, yield, sugar yield, potential alcohol content and total acidity over four successive years of treatment.</p><p style="text-align: justify;"><strong>Methods and results</strong>: At véraison, either total defoliation or total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…The accumulation of carbohydrates in storage tissues depends on total photosynthesis and the partitioning of carbon among different plant organs (Howell 2001, Smith and. In temperate climate vines, several studies have demonstrated that the majority of the carbohydrate restoration in storage tissues takes place during the post-harvest period, which supports vine reserve recovery (Bennett et al 2005, Vaillant-Gaveau et al 2014. Although the rate of photosynthetic activity decreases in line with leaf senescence (Bertamini and Nedunchezhian 2003), functional leaves remain active and help the replenishment of reserves (Scholefield et al 1978, Loescher et al 1990.…”
Section: Introductionmentioning
confidence: 98%
“…The accumulation of carbohydrates in storage tissues depends on total photosynthesis and the partitioning of carbon among different plant organs (Howell 2001, Smith and. In temperate climate vines, several studies have demonstrated that the majority of the carbohydrate restoration in storage tissues takes place during the post-harvest period, which supports vine reserve recovery (Bennett et al 2005, Vaillant-Gaveau et al 2014. Although the rate of photosynthetic activity decreases in line with leaf senescence (Bertamini and Nedunchezhian 2003), functional leaves remain active and help the replenishment of reserves (Scholefield et al 1978, Loescher et al 1990.…”
Section: Introductionmentioning
confidence: 98%
“…The two main flushes of root growth for wine grapes occur around bloom and after harvest [38,39]. As a result, post-harvest is a critical period for the restoration of carbohydrates in storage tissues to sustain the vegetative growth of vines in the following season, and to maintain yield levels [24,25]. Several studies have shown the links between the accumulation of carbohydrate reserves and yield parameters and berry weight [40][41][42]; this demonstrates that post-harvest defoliation and early leaf fall influence carbohydrate accumulation in vine roots.…”
Section: Discussionmentioning
confidence: 99%
“…After harvest, carbon assimilation is possible while vines still retain functional leaves and through until leaf fall. A loss of leaf area during this period, either due to water stress or defoliation, may therefore affect vegetative growth and yield in the following season [24,25]. To the best of our knowledge, there has so far been no study conducted with white wine grape cultivars that has evaluated the carry-over effects of adopting different RDI strategies during the post-harvest period into subsequent seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in leaf area caused by early leaf fall may negatively reflect on the production quality and/or yield. Early defoliation can result in a lower soybean grain weight, uneven grape cluster maturation and reduced growth of grapevine branches (Yang et al, 1990;Mueller et al, 2009;Sikora et al, 2014;Vaillant-Gaveau et al, 2014). In annual crops, the effects of leaf area reduction are observed in the same season, while in perennial crops, the effects may be cumulative over the years.…”
Section: Damage Caused By Rustsmentioning
confidence: 99%
“…The yield reduction is due to the low quantity of carbohydrates stored in the roots during the dormant period, and consequently, low supplies are available for plant development in the following season (Vaillant-Gaveau et al, 2014). Early defoliation is negatively correlated with yield in the same season for soybean, due to the low amount of carbohydrates translocated and stored in the grains (Mueller et al, 2009).…”
Section: Introductionmentioning
confidence: 99%